Kocbek in Mounier - Ogrin, Matija (Primerjalna književnost, 1997)
Many ideas of the French personalism can be traced in the essays of the Slovenian poet, writer and politician Edvard Kocbek (1904-1981). The study focuses on the influence of the Christian personalist Emmanuel Mounier, discussing his terminology and ideas, and presenting their reception by Kocbekin the period 1932-1940. Special attention is paid to the terms person, incarnation, engagement and testimony. It is shown that Kocbek accepted them under the strong influence of the movement generated by the magazins Križ na gori and Križ, i.e. by the Slovenian branch of the new catholic movements initiated by the European youth after World War I: it emphasized personal experience of religion and demanded man's ethical renewal. Kocbek was also influenced by the ideas of the L'Ordre nouveau group, which originated in Mounier's personalistic movement. But he differs from Mounier's understanding of the term person, so, all in all, Kocbek's thought cannot be considered as purely personalistic.
Keywords: Kocbek, Edvard, 1904-1981; Mounier, Emmanuel; Slovene literature; slovenska književnost; personalizem; vplivi; filozofija; philosophy